Destabilization of the medial meniscus to induce post-traumatic osteoarthritis in domestic pigs - Jacqueline M. Chevalier; Garett B. Pearson; Nicole Nixon; Carl R. Flannery; Luis Campoy; Lisa A. Fortier (Elsevier, 2023)
Introduction: Post-traumatic osteoarthritis (PTOA) develops following traumatic articular insult. One model system used to study the progression and treatment of PTOA is the destabilization of the medial meniscus (DMM) as first described by Glasson et al performed in mini-pigs. Miniature pigs are less available, more expensive, and have synovial fluid sampling limitations, limiting the availability of osteoarthritis biomarkers compared to domestic pigs. Objectives: The following technical note details stepwise procedures and animal welfare strategies for the use of Yorkshire pigs as a large animal PTOA model. Methods: The following technical note details stepwise procedures to perform peroperative saphenous nerve block, DMM, and subsequent postoperative management in Yorkshire pigs as a large animal PTOA model. Results: At 4 weeks post-operatively, all pigs develop mild-moderate PTOA based on postmortem joint dissections. Conclusions: This technical note provides further details on the arthrotomy approach to destabilize the medial meniscus of domestic pigs as a model of PTOA.